West Borneo International Harbour Passenger Terminal - Pertiwi, Gea; , Ronim Azizah, ST. MT (2017)
A port is a marine transportation mode, its holds a major role hearts for economic development. The existence Dwikora piers in Pontianak city is a prayer one has been used. But, it can not to support marine transportation by include activity passenger terminal for a review of embarkation and disembarkation on domestic and international passengers. Appears but the problems is when these activities already in good, so it is worth their hearts repair sector functions and meeting the needs space. The relocation process launched by the government piers on 2012 brings new port with international level. Then it is appropriate to design passenger terminal at the port area port of key West Borneo. Things can be done so that the singer follows the standard piers better from the terminal has a previous ada, as well as meet the convenience factor for users to realize the marine transportation system safe, convenient, and the process is efficient in that area.